Hypersensitive-like response in Brassica plants is specifically induced by molecules from egg-associated secretions of cabbage white butterflies - Caarls, Lotte; Bassetti, Niccolò; Verbaarschot, Patrick; Mumm, Roland; van Loon, Joop J. A.; Schranz, M. Eric; Fatouros, Nina E. (Frontiers in Ecology and Evolution, 2023)
Plants perceive and respond to herbivore insect eggs. Upon egg deposition on leaves, a strong hypersensitive response (HR)-like cell death can be activated leading to egg desiccation and/or dropping. In Brassica spp., including many crops, the HR-like mechanism against eggs of cabbage white butterflies (Pieris spp.) is poorly understood. Here, we study the cellular and molecular response in two Brassica species, the crop B. rapa and its wild relative B. nigra, to Pieris eggs. We developed a method to generate egg wash to characterize potential insect egg-associated molecular patterns (EAMPs) inducing HR-like cell death. Eggs of Pieris brassicae butterflies induced typical hallmarks of early immune responses, such as callose deposition, production of reactive oxygen species and cell death in B. nigra and B. rapa leaf tissue, also in plants that did not express HR-like cell death. However, elevated levels of ethylene production and upregulation of salicylic acid-responsive genes were only detected in a B. nigra accession expressing HR-like cell death. We found that eggs and egg wash from Pieris contains compounds inducing such responses, but not the eggs of the generalist Mamestra brassicae. Furthermore, wash made from hatched Pieris eggs, egg glue, and accessory reproductive glands (ARG) that produce this glue, induced HR-like cell death, whereas washes from unfertilized eggs dissected from the ovaries or removal of the glue from eggs resulted in no or a reduced response. This points to one or multiple EAMPs located in the egg glue and a response in B. nigra specific to Pieris species. Lastly, our results indicate that the chemical character of the EAMP is neither a protein nor a lipid. Our study expands the knowledge on the Brassica-Pieris-egg interaction and is a step closer toward identification of EAMPs in Pieris egg glue and corresponding receptor(s) in Brassica.